Wind Tunnel Testing on Start/Unstart Characteristics of Finite Supersonic Biplane Wing - Hiroshi Yamashita; Naoshi Kuratani; Masahito Yonezawa; Toshihiro Ogawa; Hiroki Nagai; Keisuke Asai; Shigeru Obayashi (International Journal of Aerospace Engineering)
This study describes the start/unstart characteristics of a finite and rectangular supersonic biplane wing. Two wing models were tested in wind tunnels with aspect ratios of 0.75 (model A) and 2.5 (model B). The models were composed of a Busemann biplane section. The tests were carried out using supersonic and transonic wind tunnels over a Mach number range of 0.3≤M∞≤2.3 with angles of attack of 0°, 2°, and 4°. The Schlieren system was used to observe the flow characteristics around the models. The experimental results showed that these models had start/unstart characteristics that differed from those of the Busemann biplane (two dimensional) owing to three-dimensional effects. Models A and B started at lower Mach numbers than the Busemann biplane. The characteristics also varied with aspect ratio: model A (1.3<M∞<1.5) started at a lower Mach number than model B (1.6<M∞<1.8) owing to the lower aspect ratio. Model B was located in the double solution domain for the start/unstart characteristics at M∞=1.7, and model B was in either the start or unstart state at M∞=1.7. Once the state was determined, either state was stable.